Estimation of Construction Cost of Road Works in Central Sulawesi Using Quadratic Regression - Andi Rizal; T. Hilmansyah; M. Fajri (Universitas Muhammadiyah Palu, 2025)
Cost estimation is an attempt to forecast or estimate the value of a job by analyzing calculations based on experience or information obtained at that time. Cost estimation has great benefits for project owners, consultants, and contractors. This research is based on cost estimates that provide great benefits to owners, contractors, and consultants, but there are often errors in cost estimates due to the lack of experience and information possessed by an estimator. The purpose of this study is to develop an equation that can guide an estimator in estimating costs with a level of accuracy that is close to the actual cost and speed up the estimation process. The method used in this study is data collection by taking directly from road projects that are in the middle of the ulawesi, data tabulias, correlation and quadratic regression. The outputs to be achieved in this study are scientific articles published in research journals and reports on the results of activities.